A ficcionalização dos sertões: discursos poéticos sobre os vales dos rios Araguaia e Tocantins - Medeiros, Olivia Macedo Miranda de (2017)
The sertões are a nationally debated theme and constitute one of the narrative tops from which Brazil was interpreted. Whether it is due to the dialogue between nation / sertão, littoral / sertão, civilization / sertão, the place of sertões has been a theme that still moves the national historiography. In this work we also intend to study the sertões, but not that generic sertão that could not be seen as a geographically specific and culturally particular place. It is a question of investigating the backlands of the Araguaia and Tocantins river valleys between the end of the 19th and the mid-20th centuries, in order to understand how, in addition to experience, they are narratively composed as language and, in this sense, are tributaries of discursive, poetic and rhetorical constructs. To conceive the sertões of the valleys as a construct of language formalizes the thesis of this work, namely, the idea that this region is a fictionalized construction constituted semantically in the interface of speeches. To carry out this proposal we base our investigation on the discussions of Carlo Ginzburg about the principles of reality; of Hayden White with his tropological theory; of Paul Ricoeur than with the conception of narrative; of Raymond Williams with the notion of sense structure; Mikhail Bakhtin with his reading about the specificities of the literary languages and Roland Barthes with the amplification of the comprehension of the notion of literature and of literary practice.